Introduction to partial differential equations: a computational approach - Tveito, Aslak; Winther, Ragnar; Marsden, Jerrold E.; Sirovich, L.; Golubitsky, Martin; Jäger, Willi (Springer-Verlag Berlin Heidelberg, 2005)
Setting the Scene -- Two-Point Boundary Value Problems -- The Heat Equation -- Finite Difference Schemes for the Heat Equation -- The Wave Equation -- Maximum Principles -- Poisson's Equation in Two Space Dimensions -- Orthogonality and General Fourier Series -- Convergence of Fourier Series -- The Heat Equation Revisited -- Reaction-Diffusion Equations -- Applications of the Fourier Transform.
Description based upon print version of record
Keywords: Numerisches Verfahren; Partielle Differentialgleichung